Specific Characteristics of Mother Language Teaching in Connection with Computer Science - Mukhtarova Shakhnoza Mashrabovna (Web of Journals Publishing, 2023)
This article discusses the integrative approach to mother tongue education at school. The article gives ideas on how to teach students to sort information from a young age by connecting the science of the mother tongue with the science of informatics, how to create self-awareness in the digital world, and how to use digital tools. It is written about the importance of assignments in school textbooks.
Keywords: integration, pedagogical technology, digitization, social networks, digital world, social media, media literacy.